Looking South : the evolution of Latin Americanist scholarship in the United States, 1850-1975 - Delpar, Helen (University of Alabama Press, 2008)
In the Preface to her new study, Latin Americanist Helen Delpar writes, "Since the seventeenth century, Americans have turned their gaze toward the lands to the south, seeing in them fields for religious proselytization, economic enterprise, and military conquest." Delpar, consequently, aims her considerable gaze back at those Americans and the story behind their longtime fascination with Latin American culture. By visiting seminal works and the cultures from which they emerged, following the effects of changes in scholarly norms and political developments on the training of students.